2019
DOI: 10.1371/journal.pone.0211900
|View full text |Cite
|
Sign up to set email alerts
|

Double arterial cannulation strategy for acute type A aortic dissection repair: A 10-year single-institution experience

Abstract: BackgroundRepair of acute type A aortic dissection (ATAAD) is a complex and emergent cardiovascular surgery that is associated with high perioperative morbidity and mortality. Each cannulation strategy has different benefits and drawbacks during cardiopulmonary bypass. Using a retrospective study design, we aimed to clarify the safety and efficacy of right axillary artery cannulation in combination with femoral artery cannulation compared to single arterial cannulation for ATAAD repair.MethodsFrom January 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
1
28
2
Order By: Relevance
“…According to previous studies [14,15], hospital mortality ranges from 43% to 54% and postoperative cerebrovascular complication rates are up to 33% in this high-risk subgroup. In the present study, we observed an inferior but acceptable outcome compared to that of our previous studies among the general ATAAD population [6,7]. High incidence of preoperative CPR and shock status may be important factors attributable for the poor outcomes.…”
Section: Impact Of Hemopericardiumcontrasting
confidence: 75%
See 2 more Smart Citations
“…According to previous studies [14,15], hospital mortality ranges from 43% to 54% and postoperative cerebrovascular complication rates are up to 33% in this high-risk subgroup. In the present study, we observed an inferior but acceptable outcome compared to that of our previous studies among the general ATAAD population [6,7]. High incidence of preoperative CPR and shock status may be important factors attributable for the poor outcomes.…”
Section: Impact Of Hemopericardiumcontrasting
confidence: 75%
“…Therefore, surgeons may try to minimize the prolonged CPB time if possible. In the institution, a double arterial cannulation with ACP strategy was commonly used in ATAAD patients with relatively stable hemodynamics [7]. However, this modality can not be a routine choice for managing this critical scenario in the present study.…”
Section: Plos Onementioning
confidence: 90%
See 1 more Smart Citation
“…The general principles of ATAAD repair procedures have been detailed in previous studies reported by our institution [ 12 , 13 ]. For patients who presented with an unstable hemodynamic status before surgery, especially those who required CPR, the femoral artery was considered a preferable choice for cannulation access to minimize the time required to establish cardiopulmonary bypass (CPB).…”
Section: Methodsmentioning
confidence: 99%
“…The general principles of aortic repair procedures are detailed in previous studies reported by this institute 10 , 11 . For uncomplicated ATAAD patients who were considered relatively stable, double arterial cannulation with antegrade cerebral perfusion (ACP) strategy was usually implemented.…”
Section: Methodsmentioning
confidence: 99%